NANOTECHNOLOGICAL APPROACH TO ENHANCE THE STABILITY AND BIOAVAILABILITY OF THE HERBAL DRUG "MURVA" - ARULANANDRAJ, N; Gopal, V; Dhivya, S; Jayabalan, G (Journal of Drug Delivery and Therapeutics, 2018)
Murva (Maerua oblongifolia) contains numerous bioactive compounds that may provide multiple health benefits, including anti-microbial, anti-fungal, anti-pyretic and anti-diabetic. Most of the therapeutic effects of murva have been attributed due to the presence of triterpenoids and alkaloids, in their composition. Although these compounds have been shown promising therapeutic effects under in-vitro conditions, they met with limited efficacy in clinical settings due to various reasons such as poor oral absorption and bioavailability. Different techniques have been proposed to improve the stability and bioavailability of the herbal drugs. Among such strategies, nanoparticulate based drug delivery systems are novel and promising tools. In this study, chitosan nanoparticles containing Murva (CNP1-CNP3) were synthesized by ionic gelation technique, which resulting in particles size smaller than 650nm. The encapsulation efficiency of nanoformulations was over 41.5%. The nanoformulations exhibited slow and sustained in vitro release over 99% of drug from the Murva encapsulated chitosan nanoparticles after 24 hours. The synthesized nanoformulations were found to be a promising system for oral sustained administration of murva and also enhances its stability and bioavailability. Keywords: Nanoparticles, Murva, chitosan, stability, bioavailability.